2013
DOI: 10.1590/s0001-37652013000100010
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pathway from leaves to galls induced by a sap-feeding insect on Schinus polygamus (Cav.) Cabrera (Anacardiaceae)

Abstract: Galling sap-feeding insects are presumed to cause only minor changes in host plant tissues, because they usually do not require development of nutritive tissues for their own use. This premise was examined through comparison of the histometry, cytometry and anatomical development of non-galled leaves and galls of Calophya duvauae (Scott) (Hemiptera: Calophyidae) on Schinus polygamus (Cav.) Cabrera (Anacardiaceae). Cell fates changed from non-galled leaves to galls during the course of tissue differentiation. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…This set of modifications was also observed in galls of Baccharopelma dracunculifolia on Baccharis dracunculifolia but does not seem to be a strict pattern, as some host plant cells could respond more widely, as reported in Isaias et al (2011), Dias et al (2013a and Carneiro et al (2014), for instance. The pectin composition of these two sets of cells changed from non-galled to galled condition, promoting properties linked to cell wall rigidity and porosity (Formiga et al 2013).…”
Section: Similarity Between Non-galled Leaves and Leaf Gallssupporting
confidence: 59%
“…This set of modifications was also observed in galls of Baccharopelma dracunculifolia on Baccharis dracunculifolia but does not seem to be a strict pattern, as some host plant cells could respond more widely, as reported in Isaias et al (2011), Dias et al (2013a and Carneiro et al (2014), for instance. The pectin composition of these two sets of cells changed from non-galled to galled condition, promoting properties linked to cell wall rigidity and porosity (Formiga et al 2013).…”
Section: Similarity Between Non-galled Leaves and Leaf Gallssupporting
confidence: 59%
“…The anatomical characters of the Lamiaceae were previously studied by Kahraman, Dogan, Celep, Akaydin, and Koyuncu () and explained its taxonomic significance. The comparative anatomy of leaves with characteristics of the transverse section of leaves has proven important use for higher complex plants in discrimination of species and also understanding of extant taxa relationships (Dias, Ferreira, Moreira, & Isaias, ; Kelleher, Simpson, & Simpson, ; Radford, Dickison, Massey, & Bell, ; Stace, ). The comparative anatomy of leaves in various genera of the Lamiaceae has been considered useful in species delimitation (Bokhan & Hedge, ; Bokhari & Hedge, ; Salmaki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Growth via tissue hyperplasia and cell hypertrophy is a common feature in galls and pseudogalls (when the insect is not enclosed within plant tissue, i.e., open galls; Zhang and Chen 1999) induced by different aphids and relatives such as Phloeomyzus passerinii , Eriosoma lanigerum , Adelges laricis , Adelges abietis , and Daktulosphaira vitifoliae , but also in other insect-induced galls in general (Elzen 1983; Brown et al 1991; Rohfritsch and Anthony 1992; Wool and Bar-El 1995; Forneck et al 2002; Kraus et al 2002; Arduin et al 2005; Álvarez et al 2009; Oliveira and Isaias 2010a; Carneiro et al 2014; Dardeau et al 2014a, b; Tooker and Helms 2014; Carneiro et al 2015; Kurzfeld-Zexer et al 2015; Suzuki et al 2015). Cell divisions occur in several planes, increasing the number of cell layers and the thickness of the parenchyma, and are related to the new functions of the mesophyll as a feeding site and a protective barrier for the insect (Mani 1964; Rohfritsch 1992; Moura et al 2008; Dias et al 2013; Carneiro et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…This study showed that P. betae galls function as physiological sinks, drawing in resources from the surrounding plant tissue (galled and surrounding leaves) leading to an accumulation of nutrients at the feeding site. The imported nutrients improve the nutritional quality of phloem sap and accumulate in the most internal cell layers (Larson and Whitham 1991; Inbar et al 1995; Fay et al 1996; Koyama et al 2004; Suzuki et al 2009; Dias et al 2013). Thus, even though the Pemphigus aphids do not consume the gall tissue, they induce changes in the plant vascular system that lead to nutrient accumulation in surrounding galled tissues.…”
Section: Discussionmentioning
confidence: 99%